Ritual practices and social interactions among tidjanites during the birth ceremony of the prophet. (The brotherhood of Ras El maa sample) - Daddi, Mohammed (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
This study aims to identify the sort of ritual practices, during the celebrations of the prophet's birthday, which connect between members of the Tidj’ania in the Algerian province, Ras al-M’aa. Further, it investigates to explain and interpret the connotations, symbols and meanings that Tidj’ani celebrants bring to these rituals. In fact, the option of this tariq’a and z’aouia was exclusively made than that of other tariq’as because the tariq’a al- Tidj’ania pays great attention to the celebration of the prophet's birthday than any others. Certainly, after investigations and exploratory and field interviews, which were applied in this z’aouia in the preliminary stage, the researcher used a non-participatory observation - It is a very appropriate research method in anthropology and ethnography. This observation lasted a day and night, that is, from preparation of celebration until the end of it. Besides, the methodology used in this research was qualitative, that is, the descriptive and analytical study.This research came up with the results that the Tidj’anis express the spirit of affiliation and strengthen the principle of solidarity, through ritual ceremonies. Therefore, as a religious group, it has its own ritual and belief features and peculiarities, and this is what makes it perceive the unity of affiliation and belief, thus, this enhances idea of ​​union and solidarity as well as the sense of harmony and integration. In addition, from the view of Tidj’anis, the celebrations are the source of relational nature, which contributes to the sacredness; even though the sanctified in them is, the essential thing whatever the nature of it is, be it a thing or creature such as, a dome or an ancestor, however, this remains only symbolic and semantic character. Consequently, the relational character confers holiness on the thing or object. As a result, this is what embodies in general in celebrations, which allows the group to consolidate and strengthen relations, establish self-confidence, and emphasizes the sincerity and validity of belief in light of the rise and growth of other Islamic sects.